Manifestation of Leaf Phenotype Character Diversity in Population Genetics Studies of Robusta Coffee (Coffea canephora) in the Gunung Betung Valley Titik Bogorejo Pesawaran Lampung: Manifestasi Keragaman Karakter Fenotipe Daun dalam Kajian Genetika Populasi Kopi Robusta (Coffea canephora) di Lembah Gunung Betung Titik Bogorejo Pesawaran Lampung - Winarno, Winarno; Priyambodo, Priyambodo; Rustiati, Elly Lestari; Lestari, Septi Wahyu; Sandra, Shifa; Thesalonika, Natasya; Ashari, Minanti Mayda; Andriyani, Yuliana; Maharani, Annisa Lidya; Afandi, Aril; Febriansyah, Muhammad; Pratiwi, Dian Neli; Permatasari, Nindy; Suhada, Suhada (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2025)
Robusta coffee (Coffea canephora) genetic diversity is very important for breeding programmes aimed at increasing yield and adaptability. This diversity can be assessed through various morphological characters, especially leaf phenotype characters, which serve as indicators of genetic variation. This research was conducted from May to August 2024. Data collection was carried out by purposive sampling using the exploration and characterisation method of 30 coffee plants in the Traditional Coffee Plantation area, Bogorejo Village, Gedong Tataan District, Pesawaran Regency, Lampung Province. Qualitative character data collection was carried out modifying IPGRI descriptors. Based on the data obtained, there were no significant differences in qualitative characteristics and quantitative characteristics of leaves on 30 coffee plants. This indicates a low genetic diversity in the plantation.